2013
DOI: 10.1007/s10067-013-2227-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent macrophage activation syndrome as the primary manifestation in systemic lupus erythematosus and the benefit of serial ferritin measurements: a case-based review

Abstract: Macrophage activation syndrome (MAS) is a fatal complication in rheumatic diseases. It is characterized by prolonged fever, pancytopenia, and hepatosplenomegaly, which are consequences of uncontrolled macrophage activation. MAS in children is most commonly associated with systemic juvenile idiopathic arthritis. Its association with systemic lupus erythematosus (SLE) is relatively rare, so we report a Thai boy who initially presented with MAS and eventually was diagnosed as having SLE. He also had recurrent MAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 22 publications
1
52
0
3
Order By: Relevance
“…In the last one year, no case of MAS secondary to another rheumatic disease was found. Macrophage activation syndrome may be triggered as a complication of an underlying disease without any triggering factor or in relation with any infection, drug change, drug side effect or initiation of biological drugs (15). No triggering factor was found in any of our patients in our study.…”
Section: Discussionmentioning
confidence: 45%
“…In the last one year, no case of MAS secondary to another rheumatic disease was found. Macrophage activation syndrome may be triggered as a complication of an underlying disease without any triggering factor or in relation with any infection, drug change, drug side effect or initiation of biological drugs (15). No triggering factor was found in any of our patients in our study.…”
Section: Discussionmentioning
confidence: 45%
“…Among 12 pediatric patients with macrophage activation syndrome as the first manifestation of SLE, 5/12 (41%) cases were as . MAS in SLE is usually fatal and MAS develops in severe SLE 10,11) . A re view of cases with pediatric MAS in lupus revealed that it was often refractory or recurrent 5,12,14,18) .…”
Section: Among the Infections Associated Mas Viral Infectionsmentioning
confidence: 99%
“…Charakterystyczna jest limfopenia, która u dorosłych występuje w AIDS, co łatwo jest wykluczyć, potwierdzając zakażenie wirusem ludzkiego niedoboru odporności HIV [19]. W koagulogramie występują takie nieprawidłowości, jak: wydłużenie czasu protrombinowego (PT) i czasu częściowej tromboplastyny po aktywacji (APTT), zmniejszenie stężenia czynników krzepnięcia II, VII, X, hipofibrynogenemia [18]. Stwierdza się zwiększone stężenia dehydrogenazy mleczanowej (lactate dehydrogenase -LDH), D-dimerów oraz ferrytyny, często powyżej 10 000 ng/ml (do różnicowania z chorobą Stilla) [20].…”
Section: Obraz Klinicznyunclassified
“…Monitorowanie stężenia ferrytyny uła-twia diagnostykę i jest stosowane jako marker ogólnego zapalenia, przydatne również w ocenie skuteczności leczenia, podobnie jak i oznaczanie poziomu β 2 -mikroglobuliny w moczu [20]. Niestety, korelacja między poziomem ferrytyny a ciężkością choroby nadal pozostaje dyskusyjna [18].…”
Section: Obraz Klinicznyunclassified
See 1 more Smart Citation